2011
DOI: 10.1049/iet-its.2010.0112
|View full text |Cite
|
Sign up to set email alerts
|

Semi-autonomous advanced parking assistants: do they really have to be learned if steering is automated?

Abstract: A few studies have demonstrated positive effects of Advanced Parking As-sists (APA) on driver comfort and parking performance. Learning effects while handling the APA system and possible transfer effects on manual parking have not been discussed yet. In this study, N = 18 subjects parked parallel in a test area (26 manoeuvres) and in real traffic (9 manoeuvres). One half of the manoeuvres was done without the parking assist, one half with a semi-autonomous APA system which utilized automatic steering. The APA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…Studies testing these types of systems in real-world settings with middle-age and older drivers have found that use of the system: reduced mental workload when parking (Tachibana 2011; Totzke et al 2010); reduced stress as measured by a reduction in heart rate (Reimer et al 2010); improved parking behavior as measured by a number of factors (Reimer et al 2010; Totzke et al 2011); rated more positively and might transfer learning so that parking will be improved even when the system is not being used (Reimer et al 2010; Totzke et al 2011; Kawabata et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Studies testing these types of systems in real-world settings with middle-age and older drivers have found that use of the system: reduced mental workload when parking (Tachibana 2011; Totzke et al 2010); reduced stress as measured by a reduction in heart rate (Reimer et al 2010); improved parking behavior as measured by a number of factors (Reimer et al 2010; Totzke et al 2011); rated more positively and might transfer learning so that parking will be improved even when the system is not being used (Reimer et al 2010; Totzke et al 2011; Kawabata et al 2008). …”
Section: Resultsmentioning
confidence: 99%
“…If the driver does not comprehend the system's behavior as it actually is, "automation surprise" occurs when the system behaves unexpectedly. Therefore, interaction concepts for these systems have to take into account phenomena such as "over trust" and "over reliance" on the system to avoid serious problems [129]. Currently, numerous ADASs are available as mature products to support longitudinal and lateral vehicle control.…”
Section: International Journal Of Vehicular Technologymentioning
confidence: 99%
“…So, the combination of those sensors cannot detect close objects. For example, the parking assistance system (PAS) prioritizes the detection of short-range objects within 1 m and sometimes uses ultrasonic sensors for detection [3]. A current ultrasonic module for vehicles calculates the distance to an object by measuring the round trip time of a transmitted pulse.…”
Section: Introductionmentioning
confidence: 99%